COMPARATIVE CHARACTERISTICS OF ANESTHESIA TYPE ON NEWBORNS’ CONDITION - Dermentli Al.; Stavrova-Hristova R.; Johanova Sl. (Science & Research)

(untitled)
Most of the drugs used in anesthesiology penetrate into placenta. This is one of the reasons for the preference of regional techniques and in particular spinal anesthesia for analgesia during cesarean section. The aim of our study was to compare the degree of neonatal depression under general and spinal anesthesia. We received the necessary information from the patients' medical history, document N2 (pre-anesthesia consultation) and the anesthesia sheet. The results show comparable newborn Apgar values under the two types of anesthesia. Much more significant factors influencing the condition of the newborn are its maturity, weight and height and intrauterine suffering of the fetus. The anesthetics used today for analgesia of operative birth have a minimal depressant effect on the fetus, although they cross the placental barrier.